The INFLUENCE OF SERVICESCAPE AND CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY WITH CUSTOMER TRUST AS AN INTERVENING VARIABLE (A Study of Customers at Empat Coffee and Spaces in Cilegon City) - lukman hidayatulloh (Management Science Research Journal, 2026)
This study aims to determine the influence of Servicescape, Customer Experience, and Customer Loyalty, mediated by Customer Trust, on consumers of Empat Coffee and Space in Cilegon City. The method used in this study is quantitative research. The population in this study were consumers of Empat Coffee and Space in Cilegon City. The sample size of this study was 168 respondents, using Purposive Sampling and Convenience Sampling methods. The data analysis technique used in this study was Structural Equation Modeling (SEM) using the SmartPLS4 analysis tool. The results of this study indicate that: (1) Servicescape has a positive and significant effect on Customer Loyalty; (2) Customer Experience has a positive and significant effect on Customer Loyalty; (3) Customer Trust has a positive and significant effect on Customer Loyalty; (4) Servicescape has a positive and significant effect on Customer Trust; (5) Customer Experience has a positive and significant effect on Customer Trust; (6) Customer Trust mediates the effect of Servicescape on Customer Loyalty; (7) Customer Trust mediates the effect of Customer Experience on Customer Loyalty.